A Severe Episode of Hemolytic Anemia After Amoxicillin Exposure in A G6PD Deficient Patient - Blanquicett, Carmelo J.; Raavi, Tapasya; Robert, Stephanie M. (Archives of Clinical and Medical Case Reports, 2019)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme deficiency worldwide, with genetic variants resulting in a range of phenotypes that vary from asymptomatic to severe hemolysis. The G6PD deficiency A- variant is associated with hemolysis., typically due to infectious or medication exposures, particularly antimalarials and sulfonamide drugs. We report a case of severe hemolytic anemia in a G6PD deficient patient whose only known exposure was amoxicillin two weeks prior to his episode of severe hemolysis, for which he presented to our hospital. An extensive infectious and hematologic workup resulted negative, with the exception of a positive G6PD deficiency result. Although rare, we suggest that the patient’s severe hemolytic anemia is probably related to amoxicillin exposure.